2005
DOI: 10.1007/s10406-005-0133-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac function and myocardial viability with 16- and 64-slice multidetector computed tomography

Abstract: Retrospectively ECG-gated MDCT shows a high correlation and acceptable agreement of left-ventricular functional parameters compared to MR imaging. Thus, in addition to the non-invasive evaluation of coronary arteries, further important additional information of left-ventricular functional parameters with clinical and prognostic relevance can be achieved by one single MDCT examination. For assessment of myocardial viability, low-dose CT late enhancement scanning is feasible, and preliminary results look promisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…In contrast, previous comparative studies on 16-slice and 64-slice CT systems versus MRI revealed a systematic deviation between −3.9±7.5% to 1.8± 4.7% for left-ventricular ejection fraction [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25]. A recent meta-analysis on studies on MDCT left-ventricular function analysis versus MRI in 252 patients revealed a (weighted) average difference of -1.7±3.1% in left-ventricular ejection fraction [35].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In contrast, previous comparative studies on 16-slice and 64-slice CT systems versus MRI revealed a systematic deviation between −3.9±7.5% to 1.8± 4.7% for left-ventricular ejection fraction [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25]. A recent meta-analysis on studies on MDCT left-ventricular function analysis versus MRI in 252 patients revealed a (weighted) average difference of -1.7±3.1% in left-ventricular ejection fraction [35].…”
Section: Discussioncontrasting
confidence: 63%
“…Those single-centre studies revealed a systematic overestimation of left-ventricular end-systolic volumes (ESV), most likely due to limited temporal resolution of the CT system used ranging between 125 to 250 ms [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Recently, phantom measurements as well as initial clinical experience on left-ventricular function assessment with 64-slice CT [21][22][23][24] and dual-source multidetector CT systems [26,27] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Using the same data for coronary CTA, two-dimensional/threedimensional (2D/3D) animation of the pulsating heart can be produced when multiple phases (e.g., 10 phases) are reconstructed. 7,8 Quantitative assessment of wall motion and systolic thickening can be evaluated and displayed with a bull's-eye map and can be pasted onto the left ventricular surface. 9 Coronary veins 10 and heart valves 11 have also become targets of multislice CT. Myocardial perfusion can also be evaluated both visually and quantitatively with Hounsfi eld units (HU), detecting hypoperfusion of the ischemic or enhanced area of the acute myocardium in a delayed scan of a contrast-enhanced study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also shown only a moderate agreement between MDCT and two-dimensional imaging techniques, such as LV angiography and echocardiography (11)(12)(13), but an excellent agreement with three-dimensional methods, such as magnetic resonance imaging (1,2,4,13). Because MDCT is a true three-dimenional imaging modality with excellent spatial and contrast resolutions, it is not surprising that functional analysis with MDCT is more accurate than two-dimensional methods compared with magnetic resonance imaging, as found by Yamamuro et al (13).…”
Section: Discussionmentioning
confidence: 97%